Computer Transactions: Potential Liability of Computer Users and Vendors - James P. Chandler (Washington University Law Quarterly, 1977)
This Article will review the social milieu in which computer liability issues arise. It will explore the alternative legal theories upon which liability of the computer manufacturer and user might be based, from the negligent use of computer information to the implied or express warranties of computer vendors. Finally, it will suggest various methods by which users and dealers might avoid or reduce their liability exposure. Professor Chandler considers the legal theories on which computer liability may be based. Although computer users may be liable in tort for negligence, a complaining party faces two difficult problems: First, the standard of “reasonable care under the circumstances” is not clearly established for computer use, and it is therefore difficult to determine negligent conduct in a particular case. In addition, unless courts recognize that a computer is usually reliable and apply the doctrine of res ipsa loquitur, a complaining party will probably be unable to prove causation of the injury by human negligence rather than unavoidable machine error. A computer user or vendor may be liable in contract if he has not clearly allocated the risks of development and performance in. the contract. He may also be strictly liable in tort or liable under an implied or express warranty theory, unless he has specifically limited his liability in the contract. Finally, Professor Chandler calls upon lawyers dealing with computer liability issues to consider what role the computer should play in our society and who should ultimately bear the risks for its development and injuries caused by it.
Keywords: Consumer transactions; Computing and the Law; Commercial law